COSMOGONIC MYTHS IN THE ORGANIZATION OF THE ADVERTISING SPACE - E. N. Ezhova (Гуманитарные и юридические исследования)
The article is devoted to the phenomenon of cosmogonic myths, which are of great significance in the organization of media-advertising world view. The author comes to the conclusion that advertising mentality is in fact mythological as it is directed on the construction of reality rather than on its reflection.